Ответы: 1
Ирина Анищенко
2017-11-15 09:16
1) (63x^2 + 49x — 81xy — 63y) — (-28x^2 — 56x — 8xy — 16y) = 63x^2 +49x -81xy — 63y + 28x^2 + 56x + 8xy + 16y) = 91x^2 + 105x — 72xy — 47y 2) (-70m^3 -90m)(5m — 8) = -350m^4 + 560m^3 -450m^2 + 720m 3) -2c(-9c — 2)(-7c — 9) = (18c^2 + 4c)(-7c — 9) = -126c^3 — 162c^2 — 28c^2 — 36c= -126c^3 — 190c^2 — 36c 4) (-7mn + 7m + 8n — 8) + (63mn + 49m — 81n — 63) = 56mn +56m — 72n — 71 5) (-25c^2 — 15c)(c + 7) = -25c^3 — 175c^2 -15c^2 — 105c = -25c^3 + 190c^2 — 105c = -25c^2 + 190c — 105